Decreased invasion of urothelial carcinoma of the bladder by inhibition of matrix-metalloproteinase 7 - Bolenz, Christian; Knauf, Daniel; John, Axel; Erben, Philipp; Steidler, Annette; Schneider, Stefan W.; Günes̃, Çag̃atay; Gorzelanny, Christian (Bladder cancer, 2018)
Objectives: To measure and to modulate the invasive potential of urothelial carcinoma of the bladder (UCB) cells in a standardized preclinical setting using broad-spectrum matrix-metalloproteinase (MMPs) inhibitors and specific targeting of MMP7. Materials and Methods: MMP expression levels in UCB cells were determined by quantitative real-time PCR (qRT-PCR) and gel zymographies of cell supernatants (MMP9, MMP2 and MMP1) and cell lysates (MMP7). The invasiveness of human UCB cells (HT1197 and T24/83) and human benign urothelial cells (UROtsa) was modulated by a broad-spectrum MMP inhibitor (4-Aminobenzoyl-Gly-Pro-D-Leu-D-Ala hydroxamic acid; AHA) and by MMP7 specific siRNAs. MMP7 knockdown efficiency was assessed by qRT-PCR and western blot. Invasive potential of UCB cells was measured by a standardized trans-epithelial electrical resistance (TEER) assay. Results: Different MMP secretion profiles were measured in UCB cells. The active form of MMP7 was exclusively detected in HT1197 cells. Characteristic TEER breakdown patterns were observed in UCB cells when compared to benign cells. Invasive potentials were significantly higher in HT1197 cells than in T24/83 and in UROtsa cells [14.8±5.75 vs. 1.5±0.56 and 1.2±0.15, respectively; p<0.01]. AHA treatment reduced the invasive potential of HT1197 cells. Also the specific downregulation of MMP7 by siRNA lowered the HT1197 cell invasiveness [20±1.0 vs. 16±2.8; p<0.05]. Neither AHA nor MMP-7 siRNA transfection altered the invasive potential of T24/83 cells. Conclusions: Invasion of UCB is partially dependent on MMPs. Specific targeting of MMP7 by siRNA reduces the invasive potential in a subgroup of UCB cells. Therefore, MMP7 represents a potential therapeutic target which warrants further investigation.
Gesehen am 07.04.2020